Hollowed or redefined? Changing visions of democracy in the political discourse of Law and Justice. Issue 3 (3rd April 2023) - Kwiatkowska, Agnieszka; Muliavka, Viktoriia; Plisiecki, Hubert
ABSTRACT: Since 2015, the governing party, Law and Justice (PiS), has gradually eroded democratic institutions in Poland. To find out whether this process has been reflected in the political discourse solely as a collapse of liberal democracy or whether we are observing a narrative redefinition of the meaning of democracy, we conducted a systematic qualitative study of the framing of democracy in PiS parliamentary speeches (2001–2020), set against the comparative background of major Polish political parties. Having adapted the Varieties of Democracy's classification of dimensions of democracy to discourse analysis, we show that while the liberal model of democracy has dominated Polish political discourse, it has been used by PiS less frequently than by other parties and in an increasingly critical way. Furthermore, electoral and majoritarian democracy has been growing in importance and the will of the electoral majority has been used to legitimize breaking democratic procedures. However, the government's broad redistributive policies have not been accompanied by a more egalitarian vision of democracy. We argue that the unwillingness to incorporate an egalitarian dimension into narratives on democracy demonstrates that the ruling party frames redistribution as their conditional charity towards selected social and occupational groups and not as a corrective towards economically inclusive democracy.